SN 2015ba: a Type IIP supernova with a long plateau. Issue 2 (21st June 2018) - Dastidar, Raya; Misra, Kuntal; Hosseinzadeh, G; Pastorello, A; Pumo, M L; Valenti, S; McCully, C; Tomasella, L; Arcavi, I; Elias-Rosa, N; Singh, Mridweeka; Gangopadhyay, Anjasha; et al.
ABSTRACT: We present optical photometry and spectroscopy from about a week after explosion to ∼272 d of an atypical Type IIP supernova, SN 2015ba, which exploded in the edge-on galaxy IC 1029. SN 2015ba is a luminous event with an absolute V -band magnitude of −17.1 ± 0.2 mag at 50 d since explosion and has a long plateau lasting for ∼123 d. The distance to the SN is estimated to be 34.8 ± 0.7 Mpc using the expanding photosphere and standard candle methods. High-velocity H Balmer components constant with time are observed in the late-plateau phase spectra of SN 2015ba, which suggests a possible role of circumstellar interaction at these phases. Both hydrodynamical and analytical modelling suggest a massive progenitor of SN 2015ba with a pre-explosion mass of 24–26 M⊙ . However, the nebular spectra of SN 2015ba exhibit insignificant levels of oxygen, which is otherwise expected from a massive progenitor. This might be suggestive of the non-monotonical link between O-core masses and the zero-age main sequence mass of pre-supernova stars and/or uncertainties in the mixing scenario in the ejecta of supernovae.